A Componential Analysis of Visual Attention in Children With ADHD. (October 2015) - McAvinue, Laura P.; Vangkilde, Signe; Johnson, Katherine A.; Habekost, Thomas; Kyllingsbæk, Søren; Bundesen, Claus; Robertson, Ian H.
Objective: Inattentive behaviour is a defining characteristic of ADHD. Researchers have wondered about the nature of the attentional deficit underlying these symptoms. The primary purpose of the current study was to examine this attentional deficit using a novel paradigm based upon the Theory of Visual Attention (TVA).Method: The TVA paradigm enabled a componential analysis of visual attention through the use of a mathematical model to estimate parameters relating to attentional selectivity and capacity. Children's ability to sustain attention was also assessed using the Sustained Attention to Response Task. The sample included a comparison between 25 children with ADHD and 25 control children aged 9-13.Results: Children with ADHD had significantly impaired sustained attention and visual processing speed but intact attentional selectivity, perceptual threshold and visual short-term memory capacity.Conclusion: The results of this study lend support to the notion of differential impairment of attentional functions in children with ADHD.